Trees in the religions of early medieval England - Bintley, Michael D. J. (Woodbridge Rochester, NY Boydell Press, 2015)
Drawing on sources from archaeology and written texts, the author brings out the full significance of trees in both pagan and Christian Anglo-Saxon religion
Frontcover; Contents; List of Illustrations; Acknowledgements; Introduction; 1. Holy Trees and Inculturation in the Conversion Period; 2. Anglo-Saxon Holy Trees and their Northern European Counterparts; 3. Rewriting the Holy Rood in Anglo-Saxon Spiritual History; 4. The Human Forest: People and Trees in Early Medieval England and Scandinavia; Bibliography; Index
Description based upon print version of record
Keywords: Trees -- England -- Religious aspects; Trees -- England -- History -- To 1500; Great Britain -- History -- Anglo-Saxon period, 449-1066; Electronic books